Evaluating the Effect of Cement and ARG Fiber on the Mechanical and Microstructural Properties of Dune Sand - Faisal I. Shalabi; Javed Mazher; Kaffayatullah Khan; Muhammad Nasir Amin; Mesfer Alqahtani; Hosam Awad; Ali Alghannam; Hussain Albaqshi (Advances in Civil Engineering)
Despite its collapsible nature and weakness, desert sand can be used for construction purposes all over the world if properly stabilized. Therefore, the aim of this study is to evaluate the effectiveness of cement and fiber in stabilizing locally available dune sand. A test plan was used to investigate the effects of varying quantities of alkali resistance glass (ARG) fiber (F: 0%, 0.2%, 0.4%, and 0.6%) and portland cement (C: 0.0%, 1.0%, 3.0%, and 5.0%) on the mechanical and microstructural properties of dune sand. Mechanical properties such as unconfined strength (UCS), strain at failure (εf), California bearing ratio (CBR), and modulus of elasticity (Es) were evaluated, and microstructure properties were investigated using Raman spectrum and laser-scanning microscopy (LSM) tests on stabilized sand samples. The results of the experimental study showed that the percentage of cement in the treated sand has a more significant impact on the investigated properties of the treated sand than the percentage of fibers. In addition, increasing fiber content results in an increase in the ductility of the sand mix. Raman analysis revealed significant interactions between sand mix components. Moreover, LSM results showed that fiber–cement interaction increased with increasing cement percentage, as calcium silicate hydrates (CSH) formed in the mix and filamentous and intrastrand binding occurred. The findings of this study indicate that ARG fiber and cement can be effective in the stabilization of dune sand for construction purposes even with the use of low percentages of ARG fiber (0.2%–0.4%) and cement (3%).